A comparative study of power production using a generic empirical model in a tidal farm (Proceedings of the European Wave and Tidal Energy Conference, 2023)
This study presents a generic model for estimating the velocity deficit and turbulence intensity ina tidal turbine farm. The proposed model considers a range of ambient turbulence intensity, the rotor diameter-to-depth ratio, and the rotor thrust coefficient in realistic applications. We evaluate the power generation of a large-scale tidal farm composed of 16 turbines in an in-line and staggered configuration in an ideal channel similar to the Alderney Race in the English Channel. The added turbulence effect is taken into account when assessing the velocity deficit in the farm. As supported by previous studies, the results show that the staggered array produces more power than the rectilinear array. The staggered arrangement benefits from flow acceleration and wide turbine spacing, which improves wake recovery. According to the results, the farm can be resized by decreasing the lateral spacing in the rectilinear array and decreasing the longitudinal spacing in the staggered array without affecting the farm’s efficiency. The reduction in farm size will reduce cable costs and provide an opportunity for future expansion. For the tidal turbines in shallow water regions, the ratio of rotor diameter to depth is shown to affect the power generated by the turbines. The power produced in the farm decreases with an increase in the rotor diameter-to-depth ratio due to the limited wake expansion along the vertical plane. This low-computational model can be useful in studying the wake interaction of tidal turbine parks in different configurations.